2018
DOI: 10.1093/hmg/ddy157
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of genome-wide research on psychotic experiences and negative symptom traits: new revelations and implications for psychiatry

Abstract: We present a systematic review of genome-wide research on psychotic experience and negative symptom (PENS) traits in the community. We integrate these new findings, most of which have emerged over the last four years, with more established behaviour genetic and epidemiological research. The review includes the first genome-wide association studies of PENS, including a recent meta-analysis, and the first SNP heritability estimates. Sample sizes of <10 000 participants mean that no genome-wide significant varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 112 publications
3
37
0
Order By: Relevance
“…Overall, molecular genetic evidence indicates a special connection between mania and thought disorder. Reality distortion – including subthreshold symptoms – and disorganization were associated with the genetic risk for schizophrenia, but these effects were modest and not specific 138‐140 .…”
Section: Validity Evidencementioning
confidence: 93%
See 1 more Smart Citation
“…Overall, molecular genetic evidence indicates a special connection between mania and thought disorder. Reality distortion – including subthreshold symptoms – and disorganization were associated with the genetic risk for schizophrenia, but these effects were modest and not specific 138‐140 .…”
Section: Validity Evidencementioning
confidence: 93%
“…The genetic coherence of the detachment spectrum has not been studied, but genetic links between detachment and thought disorder dimensions have been documented, which supports the psychosis superspectrum. Schizophrenia polygenic risk score was found to predict negative symptoms both in patients and in the general population 140‐143 . Also, anhedonia and low sociability demonstrated moderate genetic correlations with schizophrenia 144,145 .…”
Section: Validity Evidencementioning
confidence: 97%
“…These studies have focused on adolescence under the hypothesis that psychotic experiences at this age could be associated with an increased risk of mental health disorders in later life 10 . Whilst there was an initial assumption that psychotic experiences in adolescence would specifically increase the risk for schizophrenia, evidence suggests a nonspecific increased risk for a broader psychopathology 10 , suggesting that research on psychotic experiences may have an important role in understanding the pathway to a wide array of clinical diagnoses 5 . However, to date no study has found strong evidence for association between genetic liabilities for schizophrenia or any other mental disorder with psychotic experiences 7,8,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) indicate modest single-nucleotide polymorphism heritability (SNP-h 2 ) for some PENS in mid-adolescence (3%-9%) and for schizotypy in adults (20%-27%) [20][21][22] . Psychotic experiences share genome-wide genetic influences with schizophrenia and major depression 20,[23][24][25][26] , although not all studies found this, particularly those that used comparatively smaller samples or polygenic scores (PGS) from less well-powered GWAS 23,24,[27][28][29][30][31] . Schizophrenia PGS has been associated with schizotypy in adults assessed using semi-structured interviews, but not with self-rated PENS 32 .…”
Section: Introductionmentioning
confidence: 99%